Da expectativa à (des)mobilização: a trajetória da participação nas conferências da Defensoria Pública do Estado de São Paulo - Crantschaninov, Tamara Ilinsky (2018)
The expectation about participatory institutions created after the democratization of the Brazilian State in the 1980s is frustrated by the low effectiveness of these spaces in making practical the demands of social movements and civil society. This thesis studies how the resignification of democracy and popular participation, based on the construction of systemic self-references, is responsible for the demobilization around the state spaces of participation. The Public Conferences of the Public Defender’s Office of the State of São Paulo - DPESP are the case of study, since the institution is created in 2006 after extensive pressure from social movements to guarantee the model of public legal assistance. About a decade later, civil society and social movements are demobilized around the organ. However, in some specific localities, social movements continue to be mobilized for the Public Conferences, in support of the institution. The existence of these two patterns is explained by the DPESP regional nuclear model, which allows the contingency effects of social organization to be larger where it occurs. Through the narrative analysis of the actors involved in this process, as well as the use of visual and temporal bracketing techniques suggested by Langley (1999), this work advanced in the organizational theory by relating the formation and maintenance of autopoietic systems with the trajectories of dispersion and approximation of members of a system.